Penguatan Ekonomi Masyarakat Melalui Pelatihan Pembuatan Buket Snack Bagi Ibu-Ibu PKK Desa Penusupan - Fauziah, Muna; Khasanah, Uswatun; Fitriasih, Faizah; Mursilatussa’adah (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Community service activities by holding bucket-making training are one form of training held by the Penusupan Village KKN group for PKK mothers as an alternative business opportunity, where this activity is expected to increase family income with the innovation of making buckets. The purpose of this service is to improve the creativity of the Penusupan Village community and build public awareness by providing one example of many business opportunities can be applied. The methods used in the bucket-making training process include preparation, implementation, and evaluation. The results of community service in the form of bucket-making training make the Penusupan Village community, especially the PKK Penusupan Village mothers, more creative in expressing their ideas and can create business opportunities for the Penusupan Village community.